Brazil–Bolivia and a horse trade: a postcolonial case within South America. Issue 4 (4th December 2017) - Wanderley, Sergio; Celano, Ana
Abstract : Purpose: The purpose of this paper is to investigate the impact of institutional changes in Bolivia (2005-2016) in the power structures within the headquarters (HQs) of a Brazilian energy multinational corporation (MNC) and its subsidiaries in Bolivia. Design/methodology/approach: This investigation is informed by a postcolonial South–South perspective. The Brazilian and Bolivian managers were interviewed and drawing techniques were used to unveil hidden power relationships. To achieve the multilayered objective, a Lukesian power framework was integrated into the analysis. Findings: Traces of a postcolonial relationship between Brazil and Bolivia were found, even though Brazil never colonized Bolivia. The power structure within this MNC's HQ and subsidiaries reflects a postcolonial relationship: local staff members see the Brazilian MNC as the holder of power of resources, process and meaning. Finally, despite its colonizing role, Brazil is depicted as a savior, not an exploiter. Much to the authors' surprise, the institutional changes in Bolivia – the nationalization of its oil and gas reserves and the declaration of a plurinational state – have not affected the power relationships within the Brazilian MNC. Originality/value: The contribution to postcolonial investigations within the international business field was carried out in different ways: a review of EMNC literature was conducted in the study for a South–South postcolonial perspective; empirical data from a case within South America were added; a Lukesian power perspective was integrated into the analysis; and finally, drawing techniques were used to unveil hidden power relations.